2017
DOI: 10.3390/toxins9060180
|View full text |Cite
|
Sign up to set email alerts
|

Role of Homologous Fc Fragment in the Potency and Efficacy of Anti‐Botulinum Antibody Preparations

Abstract: The only approved treatment for botulism relies on passive immunity which is mostly based on antibody preparations collected from hyper-immune horses. The IgG Fc fragment is commonly removed from these heterologous preparations to reduce the incidence of hyper-sensitivity reactions. New-generation therapies entering the pipeline are based on a combination of humanized monoclonal antibodies (MAbs), which exhibit improved safety and pharmacokinetics. In the current study, a systematic and quantitative approach w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…Protection against BoNT/A light chain was observed when scFvs fused with Fc fragments (scFv-Fc) obtained from a macaque immune library were tested ex vivo [55]. Furthermore, the substantial contribution of the homologous Fc fragment to the potency of three individual anti-botulinum mAbs in antibody preparations has been demonstrated [56].…”
Section: Discussionmentioning
confidence: 99%
“…Protection against BoNT/A light chain was observed when scFvs fused with Fc fragments (scFv-Fc) obtained from a macaque immune library were tested ex vivo [55]. Furthermore, the substantial contribution of the homologous Fc fragment to the potency of three individual anti-botulinum mAbs in antibody preparations has been demonstrated [56].…”
Section: Discussionmentioning
confidence: 99%
“…Rhesus-D Ig/rhesus syndrome prophylaxis PAb (Sp IVIG) [69] Anti-toxins/botulism PAb (Sp IVIG) [70,71] Rituximab/lymphoma, Ocrelizumab/multiple sclerosis MAb (recombinant), chimeric [72,73] Infliximab/rheumatoid arthritis MAb (recombinant), chimeric [74] Nivolumab/malignant melanoma MAb (recombinant), human [75] Panitumumab/EGFR metastatic colorectal carcinoma MAb (recombinant), human [76] Daclizumab/allograft rejection Mab (recombinant), humanized [77] HpHbR Ab-PBD conjugate/African trypanosomiasis treatment (mouse model) MAb-drug conjugate [78] Vaccines MMR live attenuated viruses vaccine/measles, mumps, rubella prophylaxis PAb in vivo [79] DiTePePolHiB SU vaccine/diphtheria-tetanus-pertussis-polio-hemophilus prophylaxis PAb in vivo [80][81][82] HPV SU vaccine/cervix cancer prophylaxis PAb in vivo [83,84] CD: cluster of differentiation. DiTePePolHiB SU: Diphteria-Tetanus-Pertussis-Polio-Hemophilus influenzae B subunit vaccine.…”
Section: Therapeutics Target Neutralizationmentioning
confidence: 99%
“…Table 3 illustrates therapeutic PAb products obtained from human sera or by immunization of animals. Prominent examples are Rhesus-D PAbs (RhD Ig) used for rhesus syndrome prophylaxis and anti-botulinum toxin PAbs used for treating intoxications [69][70][71].…”
Section: Polyclonal Antibodiesmentioning
confidence: 99%
“…In this study, an HTS-based approach was applied to identify the origin of a viral pathogen found to be present in plasma obtained from a hyperimmune horse 21 . To this end, we have established a straightforward procedure that includes virus enrichment in cell culture followed by RNA extraction from the growth medium, rapid library preparation, sequencing and in-depth data analyses.…”
mentioning
confidence: 99%